Genetic confirmation of a hybrid between two highly divergent cardinalid species: A rose‐breasted grosbeak (Pheucticus ludovicianus) and a scarlet tanager (Piranga olivacea). Issue 8 (1st August 2022) - Toews, David P. L.; Rhinehart, Tessa A.; Mulvihill, Robert; Galen, Spencer; Gosser, Stephen M.; Johnson, Tom; Williamson, Jessie L.; Wood, Andrew W.; Latta, Steven C.
Abstract: Using low‐coverage whole‐genome sequencing, analysis of vocalizations, and inferences from natural history, we document a first‐generation hybrid between a rose‐breasted grosbeak ( Pheucticus ludovicianus ) and a scarlet tanager ( Piranga olivacea ). These two species occur sympatrically throughout much of eastern North America, although were not previously known to interbreed. Following the field identification of a putative hybrid, we use genetic and bioacoustic data to show that a rose‐breasted grosbeak was the maternal parent and a scarlet tanager was the paternal parent of the hybrid, whose song was similar to the latter species. These two species diverged >10 million years ago, and thus it is surprising to find a hybrid formed under natural conditions in the wild. Notably, the hybrid has an exceptionally heterozygous genome, with a conservative estimate of a heterozygous base every 100 bp. The observation that this hybrid of such highly divergent parental taxa has survived until adulthood serves as another example of the capacity for hybrid birds to survive with an exceptionally divergent genomic composition. Abstract : Using low‐coverage whole‐genome sequencing, analysis of vocalizations, and inferences from natural history, we document a first‐generation hybrid between a rose‐breasted grosbeak (Pheucticus ludovicianus) and a scarlet tanager (Piranga olivacea).